Effect of ruthenium on the precipitation of topologically close packed phases in Ni-based superalloys of 3rd and 4th generation. (15th August 2015) - Matuszewski, K.; Rettig, R.; Matysiak, H.; Peng, Z.; Povstugar, I.; Choi, P.; Müller, J.; Raabe, D.; Spiecker, E.; Kurzydłowski, K.J.; Singer, R.F.
Abstract: The precipitation of topologically close packed (TCP) phases is detrimental for the high temperature strength of high refractory Ni-based superalloys. The beneficial influence of Ru with respect to this so called instability is nowadays well accepted. In the present paper the precipitation of topologically close packed (TCP) phases is studied quantitatively in two experimental alloys (one Ru-free and one with addition of Ru) to clarify the mechanism of the Ru effect. It is confirmed that the TCP phase precipitates undergo sequential phase transformation with the tetragonal σ-phase precipitating first. Ru retards the phase transformation and leads to decreased equilibrium volume fraction of TCP phases. The results clearly indicate that Ru decreases the driving force for TCP phase precipitation. Investigations of crystallography and chemistry of the TCP/matrix interface point to an additional effect by increase of misfit strain energy.